Comparative research on (99m)Tc-Rituximab and (99m)Tc-sulfur colloid in sentinel lymph node imaging of breast cancer - Zhang, Jing-Jie (BMC Cancer, 2019)
BACKGROUND: (99m)Tc-Rituximab is a new specific radiopharmaceutical that binds to the CD20 receptor which is highly expressed on the surface of B cells. We conducted a study in which (99m)Tc-Rituximab was compared with filtered (99m)Tc-sulfur colloid (fTcSC) for sentinel lymph node (SLN) detection in patients with breast cancer. METHOD: The study is divided into three parts. 1. Initially, 25 patients were selected for an internal controlled trial to received both (99m)Tc-Rituximab and fTcSC, the interval time is separated by ≥2 days. 2. Then, 91 patients were selected for a randomized controlled trial (41 and 50 patients in the (99m)Tc-Rituximab and fTcSC groups, respectively). All patients were administered either agent at the 6- and 12-o’ clock positions by subareolar injection technique. SLN mapping was then performed 2 h after injection. 3. Serial dynamic images were further acquired for 2 h in 31 patients (22 and 9 patients from (99m)Tc-Rituximab and fTcSC cohorts, respectively). RESULTS: The identification rate of lymphoscintigraphy and SLNB in all and axilla regions for (99m)Tc-Rituximab and (99m)Tc-SC were 98.5% vs 98.7, 100% vs 98.4%, respectively. The mean number of SLNs identified by (99m)Tc-Rituximab and fTcSC was respectively 2.72 and 3.28, with a significant difference of P = 0.013 (paired sample t-test). The difference exists in the internal mammary and clavicular area, not in the axillary. The mean number of axillary sentinel lymph node biopsy (SLNB) for (99m)Tc-Rituximab and fTcSC was 2.95 vs 3.14, respectively, and no significant difference existed. (99m)Tc-Rituximab also exhibited a significantly faster injection site clearance rate when compared with fTcSC (0.193 ± 0.057 h(− 1) vs 0.021 ± 0.007 h(− 1), respectively). CONCLUSION: No significant difference was observed in identification rate and number of axillary SLN imaging and SLNB, between the two tracers. Compared to fTcSC, (99m)Tc-Rituximab based imaging demonstrated a fewer number of secondary lymph nodes and had faster injection site clearance rate. TRIAL REGISTRATION: www.chictr.org.cn, ChiCTR1900024990 (retrospectively registered August 6, 2019).